A novel application of nanohydroxyapatite/mesoporous silica biocomposite on treating dentin hypersensitivity: An in vitro study. (July 2016) - Yu, Jian; Yang, Hongye; Li, Kang; Lei, Jinmei; Zhou, Liqun; Huang, Cui
Abstract: Objectives: To fabricate a nanohydroxyapatite/mesoporous silica nanoparticle (nHAp@MSN) biocomposite and investigate its effectiveness on dentinal tubule occlusion, acid-resistant stability, and microtensile bond strength (MTBS). Methods: The nHAp@MSN biocomposite was synthesized and characterized by X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, N2 adsorption–desorption isotherms, field-emission scanning electron microscopy (FESEM), and high-resolution transmission electron microscopy (HRTEM). Thirty-two simulated sensitive dentin discs were prepared and randomly divided into four groups according to the following treatments (n = 8 each): Group 1, no treatment; Group 2, NovaMin, 15 s × 2; Group 3, MSN, 15 s × 2; Group 4, nHAp@MSN, 15 s × 2. Then, four discs per group were post-treated with 6 wt.% citric acid challenge to test their acid-resistant stability. The effects on dentinal tubule occlusion were observed by FESEM. A self-etch adhesive (G-Bond) was applied to evaluate the MTBS. The cytotoxicity was detected using the Cell Counting Kit-8 (CCK-8) assay. Results: Results revealed that the nHAp@MSN biocomposite was successfully fabricated. nHAp@MSN could effectively occlude the dentinal tubules, and the intratubular crystals were tightly associated with the tubular wall. After citric acid attack, nHAp@MSN exhibited the highest acid-resistant stability among the four groups. Moreover, no significant difference in MTBS was noted among the four groups ( P > 0.05). CCK-8 assay identified that nHAp@MSN induced no more than 20% cell death even at the highest concentration of 640 μg/mL. Conclusions: The application of the nHAp@MSN biocomposite resulted in efficient dentinal tubule occlusion, acid-resistant stability, and did not compromise immediate bond strength between dentin and self-etch adhesive system. Clinical significance: The nHAp@MSN biocomposite indicates enormous potential as a new strategy for relieving dentin hypersensitivity.